Narrative Review on Prenatal, Intrapartum and Neonatal Risk Factors for Cerebral Palsy in Children - Pranali Saurabh Thakkar; Madhavan Govindarajan Iyengar (Journal of Clinical and Diagnostic Research, 2023)
Cerebral Palsy (CP) is not a disease, however a syndrome advanced characterised by associate aberrant management of movement or posture, that seems early in life and ends up in long motor incapacity. The underlying causes of CP are still poorly understood. Many individual risk factors of CP are known, however less is understood concerning their interaction and the way they could relate to completely different pathophysiological pathways. The risk factors may be prenatal, intrapartum, neonatal or combined. Articles were searched to identify risk factors for CP, published from 2001 to 2021. A total of 43 relevant articles including randomised and non randomised controlled trials, systematic reviews and comparative studies were included in this review. From selected analysis reports, most of the studies enclosed within the review showed sturdy strength of association as a causative factor responsible for CP. From this review, it had been ended that multiple risk factors overcome the defence mechanisms and lead to CP. Although any one factor, if severe, may be sufficient to cause CP so preventive strategies and early intervention for high-risk infants are needed.